EXPERIMENTAL AND NUMERICAL INVESTIGATIONS ON THE PERFORMANCE OF S-SHAPED DIFFUSERS USING ENERGY PROMOTERS - JESSAM, RAED ABBAS (2018)
S-shaped diffusers are widely used in the air intake of aero engines. Diffusers have to be as short as possible to reduce the engine size and weight.